Serum Biomarker Profile Including CCL1, CXCL10, VEGF, and Adenosine Deaminase Activity Distinguishes Active From Remotely Acquired Latent Tuberculosis - Delemarre, Eveline M.; van Hoorn, Laura; Bossink, Aik W. J.; Drylewicz, Julia; Joosten, Simone A.; Ottenhoff, Tom H. M.; Akkerman, Onno W.; Goletti, Delia; Petruccioli, Elisa; Navarra, Assunta; van den Broek, Brigitte T. A.; Paardekooper, Sanne P. A.; et al. (Frontiers in Immunology, 2021)
Introduction: There is an urgent medical need to differentiate active (ATB) from latent tuberculosis (LTBI) and prevent under- and overtreatment. The aim of this study was to identify biomarker profiles that may support in the differentiation between ATB and LTBI and to validate these signatures. Material and Methods: The discovery cohort included adult individuals, classified in four groups: ATB (n=20), LTBI without prophylaxis (untreated-LTBI; n=20), LTBI after completion of prophylaxis (treated-LTBI; n=20) and healthy controls (HC; n=20). Their sera were analyzed for 40 cytokines/chemokines and activity of adenosine deaminase (ADA) isozymes. A prediction model was designed to differentiate ATB from untreated-LTBI using Sparse Partial Least Squares (sPLS) and logistic regression analyses. Serum samples of two independent cohorts (national and international) were used for validation. Results: SPLS regression analyses identified CCL1, CRP, CXCL10 and VEGF as the most discriminating biomarkers. These markers and ADA(2) activity were significantly increased in ATB compared to untreated-LTBI (p≤0.007). Combining CCL1, CXCL10, VEGF and ADA2 activity yielded a sensitivity and specificity of 95% and 90%, respectively, in differentiating ATB from untreated-LTBI. These findings were confirmed in the validation cohort including remotely acquired untreated-LTBI participants. Conclusion: The biomarker signature of CCL1, CXCL10, VEGF and ADA2 activity provides a promising tool for differentiating patients with ATB from non-treated LTBI individuals.